Bundesliga team values: Deciphering the impact of performance and economics. - Efehan Ulas; Christian Deutscher (PLoS ONE)
Despite experiencing a dip during the COVID-19 pandemic, football remains a robust multi-billion-euro industry. The accurate prediction of team values holds immense significance for teams, investors, and other stakeholders. In this research, we delve into the determinants of German Bundesliga team values, encompassing performance-based metrics, macroeconomic indicators, and demographic statistics. Leveraging machine learning and dynamical linear methods, we construct a comprehensive model for Bundesliga team values. Our findings not only illuminate team performance on and off the field but also offer vital insights to guide decisions and navigate the complexities of the fiercely competitive football industry.